2002
DOI: 10.1590/s0103-50532002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Concentrations in Bulk Atmospheric Deposition over the Coast of Rio de Janeiro, Southeast, Brazil

Abstract: Total Hg concentrations were measured in bulk atmospheric deposition from three sampling stations along the Rio de Janeiro State coast, Southeast, Brazil, from October 1998 to December 1999. Samples were collected at Campos dos Goytacazes, an agriculture center at the North coast; Niterói, an industrialized metropolitan area and at Itacuruçá, a tourist town at the South. Concentrations at Campos average 0.51 ng L -1 , ranging from 0.07 to 1.01 ng L -1 , and showed a seasonal trend, probably affected by burning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Furthermore, the presence of higher metal content in upper layers of the sediment core suggests that this lagoon may also have been affected by recent anthropogenic sources of trace metals. Atmospheric deposition, especially from industrial areas, can be an important source of metal contamination in coastal areas in Southeast of Brazil (Lacerda et al 2002;Lacerda and Ribeiro 2004). As there are no other industrial or urban sources in the vicinity, it may have been possible that the prevailing NE winds have transported metals released by the induration furnaces from the pelletizing plant to Guanabara Lagoon, which was previously assumed to be an undisturbed reference location.…”
Section: Sediment Normalizationmentioning
confidence: 99%
“…Furthermore, the presence of higher metal content in upper layers of the sediment core suggests that this lagoon may also have been affected by recent anthropogenic sources of trace metals. Atmospheric deposition, especially from industrial areas, can be an important source of metal contamination in coastal areas in Southeast of Brazil (Lacerda et al 2002;Lacerda and Ribeiro 2004). As there are no other industrial or urban sources in the vicinity, it may have been possible that the prevailing NE winds have transported metals released by the induration furnaces from the pelletizing plant to Guanabara Lagoon, which was previously assumed to be an undisturbed reference location.…”
Section: Sediment Normalizationmentioning
confidence: 99%
“…A seasonal trend in Hg distribution was also observed been associated with the pre-harvest burning of the sugarcane plantations. These studies suggested that for the Campos dos Goytacazes region surface ecosystems were already submitted to anomalous high deposition rates of Hg (Silva Filho, et al, 1998;Lacerda, et al, 2002). Indeed a study performed in Florida everglades sugarcane area showed that pre-harvest burning in the most significant source of Hg to that environment (Patrick et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The area was, and remains, home to some of Brazil's gold mining Bgarimpo^activity, where Hg is used in the extraction of gold from rivers and streams (Hanai 1999;Villas Bôas 2001). Atmospheric deposits also exist (Lacerda et al 2002). Together, these factors released Hg into the environment that was, and still is, available to be metabolized into methyl-Hg and incorporated into aquatic vegetation and organisms Molisani et al 1999;Yallouz et al 2001;Ferriera et al 2003;Sousa et al 2004).…”
Section: Study System-the Pairaba Do Sul Watershed and Inhabitantsmentioning
confidence: 99%